Overexpression of FERM Domain Containing Kindlin 2 (FERMT2) in Fibroblasts Correlates with EMT and Immunosuppression in Gastric Cancer - Sheng-yan Yin; Yuan-jie Liu; Jie-pin Li; Jian Liu (International Journal of Genomics)
The mesenchymal feature, dominated by epithelial mesenchymal transition (EMT) and stromal cell activation, is one of the main reasons for the aggressive nature of tumors, yet it remains poorly understood. In gastric cancer (GC), the fermitin family homolog-2 (FERMT2) is involved in macrophage signaling, promoting migration and invasion. However, the function of FERMT2 in fibroblasts remains unclear. Here, we demonstrated that downregulation of FERMT2 expression can block EMT in GC cells by inhibiting fibroblast activation in vitro. Furthermore, we found that, in addition to the known pathways, fibroblast-derived FERMT2 promotes M2-like macrophage growth and that in human GC samples, there is a strong positive correlation between FERMT2 and CD163 and CD206 levels. Notably, high FERMT2 expression was significantly associated with poor clinical outcomes and was upregulated in patients with advanced disease. Taken together, our results provide evidence that the fibroblast-FERMT2-EMT-M2 macrophage axis plays a critical role in the GC mesenchymal phenotype and may be a promising target for the treatment of advanced GC.